'Mitori' practices at a Japanese Hospital: Interactional analysis of the processes of death and dying in Japan. (April 2019) - Kawashima, Michie
Using 20 video recordings of Emergency Room treatment and over 5 years of Emergency Room fieldwork data, this study elucidates how interactional processes serve as resources for generating a cultural script of death in Japan called 'Mitori'. A sudden death at a hospital, in which a patient is removed from their social network, is often considered as the opposite of a 'good home death'. This study shows how hospital deaths in Japan are strongly interrelated with family participation. After showing the point where medical professionals decide to terminate resuscitation attempts, the analysis depicts interactional steps that shift the definition of environment from a place for treatment toward a place where 'Mitori' occurs; that is, a family encounter occurs with a dying patient. Conversation between a doctor and a family member consists of a step-by-step evidence- building story. The final section displays both conversational and physical resources used to establish 'Mitori'.